2002
DOI: 10.1080/09583150120093031
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Kudzu ( Pueraria lobata ) with an Isolate of Myrothecium verrucaria

Abstract: An isolate of the fungus Myrothecium verrucaria (MV) was evaluated for biocontrol potential against kudzu (Pueraria lobata). In greenhouse tests, MV was highly virulent against kudzu in the absence of dew when conidia were formulated in 0.2% Silwet L-77 surfactant (SW). Inoculum concentrations > 2 3 10 7 conidia ml 2 1 were required to satisfactorily control plants in the third leaf stage and larger. In controlled environment experiments, kudzu mortality was greater at higher temperatures (25-40ë C) than at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 8 publications
1
37
0
1
Order By: Relevance
“…could effectively control several common weeds under field conditions and shows potential as an effective bioherbicide for weed control in crop production systems (Boyett et al, 2007). Of these Myrothecium species, mainly M. verrucaria has been studied as a potential biocontrol agent for control of, for example, invasive climbing fern (Lygodium microphyllum), dandelion (Taraxacum officinale) (Clarke et al, 2007), kudzu (Boyette et al, 2002), and amaranth weeds including A. hybridus, A. spinosus, and A. lividus (Yang and Brenner, 1997) on the basis of their pathogenicity to host. Recent studies suggest that some Myrothecium species may serve as broad-spectrum bioherbicides (Walker and Tilley, 1997).…”
mentioning
confidence: 99%
“…could effectively control several common weeds under field conditions and shows potential as an effective bioherbicide for weed control in crop production systems (Boyett et al, 2007). Of these Myrothecium species, mainly M. verrucaria has been studied as a potential biocontrol agent for control of, for example, invasive climbing fern (Lygodium microphyllum), dandelion (Taraxacum officinale) (Clarke et al, 2007), kudzu (Boyette et al, 2002), and amaranth weeds including A. hybridus, A. spinosus, and A. lividus (Yang and Brenner, 1997) on the basis of their pathogenicity to host. Recent studies suggest that some Myrothecium species may serve as broad-spectrum bioherbicides (Walker and Tilley, 1997).…”
mentioning
confidence: 99%
“…Simple trichothecenes, such as neosoliniol monoacetate and diacetoxy-scripenol, were phytotoxic to pea seedlings, but wheat was tolerant (Brain et al, 1961). A Myrothecium verrucaria isolate that produces verrucarins also has efficacious bioherbicidal activity (Anderson and Hallett, 2004;Boyette et al, 2002;Hoagland et al, 2004;Walker and Tilley, 1997). More data and future research protocols on the development of this fungus as a bioherbicide have recently been published (Hoagland et al, 2007).…”
Section: Moniliformin Moniliformin Occurs In Isolates Of Saprophyticmentioning
confidence: 99%
“…Unless the target weed is a major problem, e.g., barnyardgrass [Echinochloa crus-galli L. Beauv] in rice, the biocontrol agent is likely to be too expensive to use for just one weed. The use of broad-spectrum bioherbicides such as Myrothecium verrucaria has recently been considered for invasive weeds such as kudzu (Pueraria lobata), which infests millions of hectares in the southeastern United States (Boyette et al, 2002). Although several plant species (Walker and Tilley, 1997) can be hosts of this pathogen, kudzu's dense growth habit and the fact that it usually doesn't flourish in extensive agronomic areas limits biological or economical concerns.…”
Section: Risks Associated With Bioherbicidesmentioning
confidence: 99%
“…Other studies in our laboratory showed MV had bioherbicidal activity against several weeds including: Kudzu (Pueraria lobata var. montana) [43], purslanes (Portulaca spp.) and spurges (Euphorbia spp.)…”
Section: Introductionmentioning
confidence: 99%